Tribo-failure characteristics of the multilayer winding hoisting wire ropes with two different structures under vibration. (October 2022) - Zhang, Qing; Peng, Yu-xing; Zhu, Zhen-cai; Chang, Xiang-dong; Lu, Hao; Zhou, Zhou; Jiang, Fan; Tang, Wei; Chen, Guo-an
Graphical abstract: Highlights: The vibration wear experiments of the two kinds of wire ropes were carried out by a self-made testing rig. The fatigue fracture of steel wire caused by fish-scales occurs under severe vibration. The main vibration wear mechanisms of the two kinds of wire ropes are abrasive wear, adhesive wear and fatigue wear. The 19 × 7 + IWS galvanized wire rope has better tribo-failure resistance. Abstract: Longitudinal vibration adversely affects the mechanical properties of the wire rope in multilayer winding hoisting system, which will further threaten the safety of hoisting. In order to master the tribo-failure characteristics of the two wire ropes with typical structures (19 × 7 + IWS galvanized wire rope and 6 × 19 + FC galvanized wire rope) under vibration, thus providing theoretical basis for the selection of wire rope in multilayer winding hoisting system, the tribological tests of the two kinds of wire ropes under vibration were carried out by a self-built vibration wear device in the present paper. The results show that the CoF (Coefficient of friction), wear degree and wear rate of the 6 × 19 + FC rope are higher than that of the 19 × 7 + IWS rope under the same vibration condition; The MTR (Maximum temperature rise) of the 6 × 19 + FC rope is basically higher than that of the 19 × 7 + IWS rope in the winding contact region; The main wear mechanisms of the two kinds of ropes are abrasive, adhesive and fatigue wear under vibration; The 19 × 7 + IWS rope has better tribo-failure resistance than the 6 × 19 + FC rope under vibration.